2007
DOI: 10.1021/tx600297u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Degradation Pathways and Kinetics of Acyl Glucuronides by NMR Spectroscopy

Abstract: Acyl glucuronides have been implicated in the toxicity of many xenobiotics and marketed drugs. These toxicities are hypothesized to be a consequence of covalent binding of the reactive forms of the acyl glucuronide to proteins. Reactive intermediates of the acyl glucuronide arise from the migration of the aglycone leading to other positional and stereoisomers under physiological conditions. In order to screen for the potential liabilities of these metabolites during the early phase of pharmaceutical developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 25 publications
4
57
0
Order By: Relevance
“…The 1.3-and 6-fold GSTcatalyzed increase in MFA-SG formation rates from reactions of MFA-SCoA and MFA-1-␤-O-G with GSH is consistent with the weak catalysis observed in previous studies with clofibric acid derivatives, where rat liver GST-mediated catalysis was shown to occur in incubations of clofibryl-1-␤-O-G (ϳ8-fold; Shore et al, 1995) and clofibryl-S-acyl-CoA (ϳ3-fold; Grillo and Benet, 2002) with GSH forming clofibryl-S-acyl-GSH thioester. In addition, we determined MFA-SCoA to be chemically stable in buffer at pH 7.4 and 37°C over 15 h of incubation, whereas MFA-1-␤-O-G degraded with a t 1/2 of 16.5 h, which was the same as reported previously (McGurk et al, 1996;Walker et al, 2007). The degradation of MFA-1-␤-O-G in buffer is known to occur almost exclusively through acyl migration and not by hydrolysis (Walker et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The 1.3-and 6-fold GSTcatalyzed increase in MFA-SG formation rates from reactions of MFA-SCoA and MFA-1-␤-O-G with GSH is consistent with the weak catalysis observed in previous studies with clofibric acid derivatives, where rat liver GST-mediated catalysis was shown to occur in incubations of clofibryl-1-␤-O-G (ϳ8-fold; Shore et al, 1995) and clofibryl-S-acyl-CoA (ϳ3-fold; Grillo and Benet, 2002) with GSH forming clofibryl-S-acyl-GSH thioester. In addition, we determined MFA-SCoA to be chemically stable in buffer at pH 7.4 and 37°C over 15 h of incubation, whereas MFA-1-␤-O-G degraded with a t 1/2 of 16.5 h, which was the same as reported previously (McGurk et al, 1996;Walker et al, 2007). The degradation of MFA-1-␤-O-G in buffer is known to occur almost exclusively through acyl migration and not by hydrolysis (Walker et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Since reaction mixture was incubated for 20 minutes in the MRP2-mediated transport experiment, part of the 1-Ob-glucuronides probably decomposed. Based on the published degradation rate constants or elimination half-lives of glucuronides at pH 7.4 (Iwaki et al, 1998;Walker et al, 2007;Sawamura et al, 2010), the remaining unchanged 1-Oglucuronides are calculated to be 68%-72% for diclofenac glucuronide, 81% for R-naproxen glucuronide, 89%-93% for S-naproxen glucuronide, and 92% for rac-ibuprofen glucuronide after 20-minute incubation at pH 7.4. We re-evaluated the stability of the glucuronides in the reaction buffer used in a MRP-mediated transport experiment.…”
Section: Nsaids-glucuronide Inhibit Methotrexate Excretion Via Mrp2/4mentioning
confidence: 99%
“…Fraction A (500 ml) was stopped by adding 500 ml of ice-cold acetonitrile containing 10% (v/v) of acetic acid, as acyl migration may be stabilized under an acidic condition (pH , 4.0) according to previous publications (Walker et al, 2007;Di Meo et al, 2013). The sample was mixed thoroughly and then centrifuged at 16,000g at 4°C for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the application of the acyl migration method to assess reactivity of those compounds for ranking and selection may provide misestimated results. However, the acyl migration method was still applicable to a majority of drugs that have acyl glucuronide issues, as it has been reported that acyl migration was identified as the predominant reaction occurring in vitro (Walker et al, 2007). More importantly, the acyl migration method can provide preliminary reactivity information in a rapid screening assay that can be used to support the selection of low-risk drug candidates in the drug discovery phase that do not depend on authentic standards.…”
Section: Fda 2008mentioning
confidence: 99%